Digital health governance in China by a whole-of-society approach - Minmin Wang; Xinran Lu; Yeting Du; Zhiqi Liu; Xiangning Li; Xuetong Zhao; Jinsheng Wang; Yinzi Jin; Minghui Ren (npj Digital Medicine)
Abstract In this study, we review the application of digital technologies for health in China, examining the structure of its digital health governance. China’s digital health governance is of political commitment, cross-sectoral collaboration, and a comprehensive, all-encompassing approach that engages the entire society. However, the fragmentation of data remains a fundamental obstacle. The whole-of-society approach offers a valuable example for other low- and middle-income countries in promoting digital transformation.